The impact of lifestyle interventions targeting physical activity and healthy diet on treatment of Obstructive Sleep Apnea (OSA): Review - Lipska, Julia; Hamerska, Laura; Hamerska, Julia; Bocianiak, Bogumił; Antczak, Joanna; Kajka, Anna; Fenrych, Urszula; Wojtczak, Karolina; Skupińska, Olga; Ruta, Damian (Quality in Sport, 2024)
Introduction and purpose: Obstructive Sleep Apnea Syndrome (OSAS) is a worldwide prevalent sleep-related medical condition characterised by upper airway collapse, leading to hypoxia and hypercapnia. Excess body weight is the risk factor of OSAS. Lifestyle interventions, particularly targeting weight loss, have emerged as potential management strategies for OSAS. The purpose of this review is to compile the information about the effectiveness of different forms of lifestyle interventions in the treatment of OSA. Brief description of the state of knowledge: While CPAP remains the current “gold standard” treatment of Obstructive Sleep Apnea, it’s not always well-tolerated. Consequently, lifestyle interventions such as dietary modifications, exercise programs, and behavioural therapies have emerged as important components in the management of this disease. The research has shown that these strategies not only reduce the severity of OSA but also improve quality of life. Summary: Lifestyle interventions, including dietary modifications, exercise programs, and behavioral therapies targeting weight loss, have demonstrated promising results in reducing the severity of obstructive sleep apnea (OSA) and alleviating associated symptoms. However, further large-scale, long-term studies are necessary to validate their efficacy and understand their broader impact on OSA management.